Pengetahuan ibu, pola makan dan status gizi pada anak stunting usia 1-5 tahun di Kelurahan Bangetayu, Kecamatan Genuk, Semarang - Margawati, Ani; Astuti, Astri Mei (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2018)
Background : Age under five years is a gold period. In the community, stunted children usually are less aware since they are aware the height of the children in their aged are not serious problem. Objective : The purpose of this study is to analyze the knowledge of mother about stunting and correlation between food intake with nutritional status among stunted children in Bangetayu village, Genuk Municipality, Semarang.Method : The design study was observational with cross sectional approach and the methods took by combination between quantitative and qualitative research methods. Populations study were children aged 1 – 5 years children who live in the study sites. Sampling technique was done by consequtive sampling technique. Sampling frame was taken from data of 6 Posyandu in Bangetayu Wetan Village and 3 Posyandu in Bangetayu Kulon and got 36 subjects. Quantitative data covering respondent characteristics and food intake were analyzed by computer, while the qualitative data were analyzed with content analysis.Result : The results showed that the mothers whose child suffered stunting not too worried about the condition of his child. Stunting is not a serious issue that needs to be handled properly. There was no correlation between food intake with nutritional status among stunted children in Bangetayu. Conclusion : The mother has wrong knowledge about stunting. There was no correlation between food intake with nutritional status among stunted children in Bangetayu.